The Evolving Hospital Market in China After the 2009 Healthcare Reform - Jiang, Qingling (Inquiry, 2020)
Since the initiation of national healthcare reform in 2009, China’s hospital market has witnessed significant change. To provide a brief description about its evolving process, China Health Statistical Yearbook data and Sichuan administrative data from 2009 to 2017 were used in this article. An overall upward trend of hospital delivery capacity was found in this study, which increased from 3.12 million beds and 1.09 million doctors in 2009 to 6.12 million and 1.80 million in 2017, respectively, while the primary healthcare institutions presented fairly slow development pace. Growing proportion of medical resources and patients gathered in hospitals, especially tertiary hospitals. While private hospitals demonstrated an increasingly important role in hospital market with growing share of capacity and service, their average capacity, especially the human resource, was found to be much lower than that of public hospitals and the gaps are still widening. The competition among hospitals grouped by homogeneous ownership types has predominated the increasingly intensified hospital market competition in China. In order to adapt to the raising demand of health care in China, it is highly recommended that strategies forged at governmental levels be focused on primary care promotion, guiding the development of private hospitals as well as on promoting orderly competition in the hospital market.